Overcoming Challenges in Higher Education: Design Thinking as a Tool for Innovation During Crises - Madhav Murthy, D N Murthy (European Economic Letters (EEL), 2024)
Design thinking is a user-centric and iterative approach to defining and tackling problems. It offers a creative yet structured approach for addressing large-scale challenges in higher education. Design thinking is a problem-solving methodology that has gained popularity in recent years due to its effectiveness in generating innovative solutions to complex problems. In the context of higher education, design thinking has become increasingly relevant in the face of crises such as the COVID-19 pandemic, which has disrupted traditional teaching and learning methods. The crises in higher education could include access, affordability, equity, and quality thinking problems, failure to adapt to the increasing need for higher level learning, quality of teaching and learning, decline of the efficacy of a college degree as a guarantee of value, etc. This article explores the concept of design thinking and its potential to serve as a catalyst for innovation in higher education during crises. It will also examine the challenges faced by higher education during crises and showcase through examples that demonstrate the successful application of design thinking in higher education. Finally, the article will discuss the benefits and impact of adopting design and acknowledge the limitations and challenges of its implementation.